Pelatihan Strategi Pemasaran Berbasis E-Commerce dalam Menumbuhkan Jiwa Wirausaha pada Generasi Muda - Gultom, Pesta; Sinaga, Hommy Dorthy Ellyany; Januarty, Widalicin (Jurnal Pengabdian Pada Masyarakat METHABDI, 2025)
One of the objectives of the Pancasila Student Profile Strengthening Project (P5) of the independent curriculum is to provide students with additional knowledge and skills from their surrounding environment. Community service was carried out for 70 10th grade students of SMA WR Supratman 1 Medan. The purpose of the Community Service activity is to provide training in making ecoprint tote bags as an implementation of the P5 independence curriculum, and to provide training in e-commerce-based marketing strategies. The benefits of this Community Service activity are that students as the younger generation have the creativity to be able to create their own work independently, namely making ecoprint tote bags that have a selling value that can be used as an entrepreneurial opportunity, and students learn more about the benefits of e-commerce as one of the digital marketing strategies.